2018
DOI: 10.3386/w25218
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Congestion in Urban India

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 6 publications
2
21
0
1
Order By: Relevance
“…Angel and Franco (2018) theorizes about the impacts of urban shapes, and concludes that both population density and compactness should affect travel distances. This hypothesis is confirmed by Akbar et al (2018), who compare average commuting outcomes across cities in India. These authors find that the shape non-convexities induced by hilly terrain and water bodies are associated with slower traffic on average.…”
Section: Introductionmentioning
confidence: 63%
“…Angel and Franco (2018) theorizes about the impacts of urban shapes, and concludes that both population density and compactness should affect travel distances. This hypothesis is confirmed by Akbar et al (2018), who compare average commuting outcomes across cities in India. These authors find that the shape non-convexities induced by hilly terrain and water bodies are associated with slower traffic on average.…”
Section: Introductionmentioning
confidence: 63%
“…The city is characterised by rising incomes, poor public services and severe traffic congestion. Akbar et al (2018) reported that Indian cities are congested throughout the day, not just during peak hours; in Bengaluru, this has led to leading firms in the city threatening to relocate elsewhere, since the city’s poor infrastructure and traffic jams are affecting employee productivity.…”
Section: Study Areamentioning
confidence: 99%
“…Fourth, the approach we develop here is an important stepping stone towards measur-ing accessibility, which is ultimately relevant to welfare. 7 In our companion paper (Akbar, Couture, Duranton, and Storeygard, 2018), we rely on the mobility (speed) index developed here as key component of an analogous accessibility (travel time) index. The other key component of accessibility is a proximity (distance to destinations) index, which also builds on the approach that we develop here.…”
Section: Introductionmentioning
confidence: 99%